DW VECSEL - structure design and MBE fabrication - Jasik, Agata; Muszalski, Jan; Wójcik-Jedlińska, Anna; Kubacka-Traczyk, Justyna; Wasiak, Michał; Sokół, Adam K.; Sankowska, Iwona (Photonics Letters of Poland, 2013)
We demonstrate dual-wavelength emission from optically pumped vertical-external-cavity surface-emitting laser. The active region containing two sets of quantum wells is divided into two sections with thicknesses providing comparable pump absorption. The sections are separated by an AlAs blocking layer to prevent carrier flow between them. The structure was grown by molecular beam epitaxy. The continuous wave operation was simultaneously detected at 957 nm and 1011 nm. Full Text: PDF References Y. Morozov, I. Nefedov, and V. Aleshkin, "Nonlinear frequency conversion in a double vertical-cavity surface-emitting laser", Semiconductors 38, 1350 (2004). CrossRef T. Leinonen, Y. A. Morozov, A. Harkonen, and M. Pessa, "Vertical external-cavity surface-emitting laser for dual-wavelength generation", IEEE Photon. Technol. Lett. 17, 2508 (2005). CrossRef Y.A. Morozov, T. Leinonen, A. Härkönen, and M. Pessa, "Simultaneous Dual-Wavelength Emission From Vertical External-Cavity Surface-Emitting Laser: A Numerical Modeling", IEEE J. Quantum Electron. 42, 1055 (2006). CrossRef Y.A. Morozov, I.S. Nefedov, T. Leinonen, and M.Y. Morozov, "Nonlinear-optical frequency conversion in a dual-wavelength vertical-external-cavity surface-emitting laser", Semiconductors 42, 463 (2008). CrossRef T. Leinonen, S. Ranta, A. Laakso, Y.A. Morozov, M. Saarinen, and M. Pessa, "Dual-wavelength generation by vertical external cavity surface-emitting laser", Opt. Express 15, 13451 (2007). CrossRef M.Y. Morozov, Y.A. Morozov, and V.V. Popov, "Effect of pump wave reflections on the excitation of a dual-wavelength vertical-cavity surface-emitting laser", Semiconductors 43, 382 (2009). CrossRef Y.A. Morozov, M.Y. Morozov, and I.V. Krasnikova, "Pulsed difference frequency generation regime in dual-wavelength vertical-external-cavity surface-emitting laser", Tech. Phys. Lett. 37, 1112 (2011). CrossRef A.C. Troppera and S. Hoogland, "Extended cavity surface-emitting semiconductor lasers", Progress in Quantum Electron. 30, 1 (2006). CrossRef L. Fan, M. Fallahi, J. Hader, A.R. Zakharian, J.V. Moloney, W. Stolz, S.W. Koch, R. Bedford, and J.T. Murray, "Linearly polarized dual-wavelength vertical-external-cavity surface-emitting laser", Appl.Phys.Lett. 90 181124 (2007). CrossRef S. Ranta, T. Leinonen, A. Härkönen, A. Laakso, Y. Morozov, and M. Pessa, "Simultaneous dual-wavelength generation from vertical external-cavity surface-emitting semiconductor lasers", Lithuanian J.Phys. 50, 27 (2010). CrossRef